Treatment and clinical outcomes of pediatric autoimmune hemolytic anemia: real-world single-center data from Korea - Young Dai Kwon; Eun Sun Jung; Yeon Jung Lim (Clinical and Experimental Pediatrics, 2025)
Background Autoimmune hemolytic anemia (AIHA) is rare and characterized by hemolytic anemia with a positive direct antiglobulin test result after the exclusion of other causes. While adults often relapse within 1 year of first-line steroid therapy, children generally respond well. However, current treatment approaches lack substantial evidence and are primarily expert opinion-based. Purpose This study aimed to contribute our single-center experience to pediatric AIHA treatment guidelines. Methods Between January 2012 and June 2024, 475 children were diagnosed with anemia; of them, 18 had immune hemolytic anemia, including 6 with neonatal alloimmune hemolytic anemia, 2 who were treated at other centers, and 2 with transient bone marrow suppression due to a viral infection. Thus, this study retrospectively analyzed the treatment responses of 8 patients with AIHA. Results The median age at diagnosis was 5.2 years (range, 2.3–11.8 years); 62.5% (5 of 8) were male. Median hemoglobin (Hb) at diagnosis was 6.3 g/dL (range, 3.4–9.5 g/dL), median reticulocyte index was 6.53% (range, 1.64%–22.07%), median total bilirubin was 2.75 mg/dL (range, 0.98–7.23 mg/dL), and median lactate dehydrogenase was 1,662 U/L (range, 790–2,921 U/L). All haptoglobin levels were <10 mg/dL. Treatments included steroids (8 of 8), red blood cell transfusions (5 of 8), and intravenous immunoglobulins (2 of 8). Half of the steroid-treated patients received intravenous methylprednisolone for 1–5 days, while half received oral prednisolone (median, 1.78 [range, 0.79–3.39] mg/kg/day). The median time to age-adjusted normal Hb levels was 16.5 days (range, 9.0–22.0 days). Steroids were administered for a median 37.5 days (range, 14.0–119.0 days). Excluding one patient later diagnosed with systemic lupus erythematosus, no relapses occurred during the 3- to 19-month follow-up period. Conclusion Patients with pediatric AIHA showed relapsefree rapid hematological improvement and sustained steroid responses within 2 months, suggesting that systematic steroid treatment is feasible and highlighting the need for multicenter trials to establish standardized guidelines.